Factors Contributing to Industrial Conflicts within Higher Education Institutions in Lesotho: A Case of the National University of Lesotho - Mojalefa, Mamoeletsi Limakatso (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Incidences of industrial actions, which have frequently paralyzed learning at most of the educational institutions, are frequent in Lesotho. Despite the safeguards for collective bargaining in Lesotho, the incidences of industrial actions at higher institutions of learning in Lesotho are still common. The study was conducted to investigate the factors which contribute to industrial conflict at the National University of Lesotho. In order to gain a deeper understanding of the participants’ unionism experiences, semi-structured interviews were used to collect data. This study reveals that lack of transparency, inconsistent application of policies, lack of communication, lack of motivation, poor salaries, bias as well as poor working conditions are some of the factors that cause strikes at the institutions of higher learning in Lesotho.